Foundations of Control: New Zealand Building Legislation in the 1840s - Isaacs, Nigel (Architectural History Aotearoa, 2014)
The development of the "Raupo Houses Ordinance 1842" could be considered as the direct ancestor of today’s "New Zealand Building Code." Limited in its scope and application, the Ordinance provided a short-term solution to what was hoped to be a short-term problem - the use of highly flammable material for house construction. It was not intended for application to the countryside, only to urban areas. To be effective, the Ordinance had to be adopted by each provincial council as covering a specific area. This occurred from 1842 (Auckland) to 1852 (Lyttelton and Christchurch). It was finally repealed in 1878. Not every province was happy with the Ordinance, with New Plymouth setting up its own "Thatch and Straw Building Ordinance." This paper will examine the intent, content and context of the Ordinance and its consequences on the development of future building controls.